2021
DOI: 10.3390/catal11020234
|View full text |Cite
|
Sign up to set email alerts
|

W-Doped ZnO Photocatalyst for the Degradation of Glyphosate in Aqueous Solution

Abstract: In this paper, the photocatalytic degradation of glyphosate by zinc oxide (ZnO) photocatalysts doped with tungsten (W) was investigated under solar simulated light. The photocatalysts were successfully synthesized through a simple precipitation method and subsequently characterized by different techniques: Raman spectroscopy, UV–Vis, N2 adsorption at −196 °C, X-ray diffraction, and SEM analysis. In particular, all the prepared catalysts were characterized by a crystallite size of about 28 nm and a hexagonal wu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 64 publications
1
5
0
1
Order By: Relevance
“…The characteristic diffraction peaks of ZnO at 2Θ = 31.7 • , 34.5 • , 36.2 • , 47.5 • , 56.6 • , 62.9 • , and 68.0 • correspond to (100), (002), ( 101), ( 102), (110), (103), and (112) crystal planes, respectively. This is totally consistent with the XRD analysis of ZnO reported in the literature [54][55][56]. It can be observed that the predominant crystal plane is (002), commonly found in the films deposited by sputtering technique due to the minimum surface energy of (002) which results in higher crystallites orientation rate along the c-axis [57][58][59].…”
Section: Structural Analysissupporting
confidence: 90%
“…The characteristic diffraction peaks of ZnO at 2Θ = 31.7 • , 34.5 • , 36.2 • , 47.5 • , 56.6 • , 62.9 • , and 68.0 • correspond to (100), (002), ( 101), ( 102), (110), (103), and (112) crystal planes, respectively. This is totally consistent with the XRD analysis of ZnO reported in the literature [54][55][56]. It can be observed that the predominant crystal plane is (002), commonly found in the films deposited by sputtering technique due to the minimum surface energy of (002) which results in higher crystallites orientation rate along the c-axis [57][58][59].…”
Section: Structural Analysissupporting
confidence: 90%
“…The WV-MNPs were used for the antimicrobial activity of the Escherichia coli bacterial strain and to find out the inevitable photodegradation of CR as well as glyphosate. In terms of performance, the newly designed photocatalyst outperformed various previously reported catalysts applied for the degradation of targeted pollutants. ,, …”
Section: Introductionmentioning
confidence: 88%
“…In terms of performance, the newly designed photocatalyst outperformed various previously reported catalysts applied for the degradation of targeted pollutants. 25,33,34 2. EXPERIMENTAL SECTION 2.1.…”
Section: Introductionmentioning
confidence: 99%
“…The excellent photocatalytic efficiency was explained as due not only to the morphology and defectivity, but also on the role of bonded citric acid as electron donor, fostering the regeneration of Ce 3+ sites by ligand-to-metal charge transfer. On the other hand, W-doped ZnO showing large wurtzite crystallites was prepared by a simple precipitation method and tested in PMG photodegradation under simulated solar light [110]. The optimal doping amount was found to be 1.5 mol%, providing 74% removal and 30% mineralization in 180 min with 1.5 g/L catalyst dosage.…”
Section: Glyphosatementioning
confidence: 99%